GREEN SYNTHESIS AND CHARACTERIZATION OF ZNO NANOPARTICLES FROM PHYLLANTHUS NIRURI AND THEIR INCORPORATION INTO BIOFILMS FOR ACTIVE FOOD PACKAGING - Kongara Gnaneswari, M. Bhargavi, T.K. Padmaja, A. Shobha, K. Manjula, Vani Mathakala (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Green nanotechnology is gaining a lot of attention as a result of the growing need for non-toxic and sustainable materials in food packaging. This work used Phyllanthus niruri leaf extract as a natural reducing and stabilizing agent to create zinc oxide nanoparticles (ZnO NPs) in an environmentally friendly manner. The formation, crystalline, functional groups, and surface shape of the bio synthesized ZnO NPs were confirmed by means of UV-Vis spectroscopy, FTIR, XRD, and SEM. The nanoparticles had favorable physicochemical characteristics that made them appropriate for use in antibacterial applications. The ZnO NPs were then added to a matrix made of bio polymers to create a biofilm that might be used in active food packaging. The mechanical characteristics, water vapor permeability, and antibacterial efficacy against food borne pathogens of the produced biofilms were assessed. The potential of ZnO NP-enriched biofilms as an efficient active packaging material was shown by the results, which showed improved barrier qualities and increased antibacterial activity. In addition to extending food safety and shelf life, this environmentally friendly strategy supports plant-based nanotechnology-based sustainable packaging solutions.